Hyperlipidemia-induced hepassocin in the liver contributes to insulin resistance in skeletal muscle. (15th July 2018) - Jung, Tae Woo; Chung, Yoon Hee; Kim, Hyoung-Chun; Abd El-Aty, A.M.; Jeong, Ji Hoon
Abstract: Hepassocin (HPS) has recently been identified as a novel hepatokine that causes hepatic steatosis. However, the role of HPS in the development of insulin resistance in skeletal muscle under obesity remains unclear. The effect of hyperlipidemia on hepatic HPS expression was evaluated in primary hepatocytes and liver of mice. HPS-mediated signal pathways were explored using small interfering (si) RNAs of specific genes or inhibitors. We found that treatment of primary hepatocytes with palmitate could induce HPS expression through C/EBPβ-mediated transcriptional activation. Furthermore, increased HPS expression was observed in the liver of high fat diet (HFD)-fed or tunicamycin-treated mice. Pretreatment with 4-phenylbutyrate (4-BPA) (an endoplasmic reticulum (ER) stress inhibitor) and suppression of p38 by siRNA abrogated the effect of palmitate on HPS expression in primary hepatocytes. Treatment of differentiated C2C12 cells with recombinant HPS caused c-Jun N-terminal kinase (JNK) phosphorylation and impairment of insulin sensitivity in a dose-dependent manner. siRNA-mediated suppression of JNK reduced the effect of HPS on insulin signaling. Furthermore, the suppression of epidermal growth factor receptor (EGFR) by siRNA mitigated both HPS-induced JNK phosphorylation and insulin resistance. In addition, HPS did not affect inflammation and ER stress in differentiated C2C12 cells. In conclusion, we elucidated that ER stress induced by palmitate could increase the expression of HPS in hepatocytes and further contribute to the development of insulin resistance in skeletal muscle via EGFR/JNK-mediated pathway. Taken together, we suggest that HPS could be a therapeutic target for obesity-linked insulin resistance. Graphical abstract: Highlights: Palmitate augmented hepassocin (HPS) expression in hepatocytes. ER stress, p38, and C/EBPβ contributed to induction of HPS expression in hepatocytes. HPS impairs insulin sensitivity in skeletal muscle via EGFR/JNK-dependent pathway.